Exploring the Role of Artificial Intelligence in Enhancing Student Motivation and Cognitive Development in Higher Education - Elbadiansyah; Zohaib Hassan Sain; Uthman Shehu Lawal; Chanda Chansa Thelma; Aulia Luqman Aziz (Pusat Riset dan Inovasi Nasional Mabadi Iqtishad Al Islami, 2024)
Artificial Intelligence (AI) has significantly transformed higher education in recent years by enhancing teaching methods and influencing student learning outcomes. This study investigates the effects of AI on student motivation and cognitive skills, addressing both the benefits and challenges of AI integration. The research adopts a mixed-methods approach, combining a comprehensive literature review with a questionnaire-based survey of 60 university students from diverse academic disciplines. The results indicate that AI tools, such as intelligent tutoring systems and learning analytics, increase student engagement, motivation, and problem-solving abilities. However, concerns regarding over-reliance on AI reduced creativity, and ethical issues such as privacy and fairness persist. This study highlights the potential of AI to foster personalized learning while emphasizing the need for responsible AI implementation to address its limitations.